The Permanence of the Political : a Democratic Critique of the Radical Impulse to Transcend Politics. - Schwartz, Joseph M. (Princeton University Press, 2001)
Why have radical political theorists, whose thinking inspired mass movements for democracy, been so suspicious of political plurality? According to Joseph Schwartz, their doubts were involved with an effort to transcend politics. Mistakenly equating all social difference with the harmful way in which particular interests dominated marketplace societies, radical thinkers sought a comprehensive set of "true human interests" that would completely abolish political strife. In extensive analyses of Rousseau, Hegel, Marx, Lenin, and Arendt, Schwartz seeks to mediate the radical critique of democrati.